Multifaceted Analysis of Landfill Gas Use for Energy Purposes - Bernard Knutel; Błażej Gaze; Krzysztof Zając; Sara Góraj; Przemysław Bukowski (Energies, 2022)
This paper assesses the use of gas from a landfill located in Kiełcz for energy purposes, considering energy, environmental and socioeconomic aspects. The literature review contains information on waste management methods in various regions of the world and the legal acts regulating them. The reference was also made to the methods of degassing landfills and the methods of reducing pollutants from this process. The research methodology describes, among other things, the method of measuring exhaust gas quality and temperature or gas composition. This section also presents the catalyst that was used as a reducer of flue gas emissions. The use of a catalyst in the flue gas duct allowed for the reduction in CO emissions by 85%, NOX by 53%, SO2 by 95%, and PM by 82%. For the socio-economic analysis, formulas and quantities were given that allow for the parameterization of profits. Three leading indicators were selected, i.e., the impact of the energy produced on the producer, the reduction in greenhouse gases, and the responsibility for the product. The section of results graphically presents the efficiency of using the catalyst. This part also contains a summary table of the socioeconomic analysis on the basis of which the social profit index SROI was determined, which amounted to 7.57. This analysis may be helpful for landfill managers/owners who may consider the potential commercial use of landfill gas for energy purposes, as well as for governments, which, amid the current global fuel crisis, can benefit from this analysis and include the use of landfill gas in their energy transition strategies.